Mongolian pine forest decline by the combinatory effect of European woodwasp and plant pathogenic fungi - Lixiang Wang (Nature Portfolio, 2021)
Abstract Interactions between the decline of Mongolian pine woodlands and fungal communities and invasive pests in northeastern China are poorly understood. In this study, we investigated the fungal communities occurring in three tree samples: the woodwasp Sirex noctilio infested, healthy uninfested and unhealthy uninfested Mongolian pine trees. We analyzed the relationships of the Mongolian pine decline with fungal infection and woodwasp infestation. Twenty-six fungal species were identified from the sampled trees. Each tree sample harbored a fungal endophyte community with a unique structure. Pathogenic fungi richness was four times higher in infested and unhealthy un-infested trees compared to that in healthy uninfested trees. Sphaeropsis sapinea was the most dominant pathogenic fungus in the sampled Mongolian pine trees. The number of S. noctilio was higher than native bark beetles in the declining Mongolian pine trees. The invasion of the woodwasp appeared to be promoted by the fungal infection in the Mongolian pine trees. The incidence of S. noctilio infestation was higher in the fungi infected trees (83.22%) than those without infection (38.72%). S. sapinea population exhibited positive associations with within-tree colonization of S. noctilio and bark beetle. Collectively, these data indicate that the fungal disease may have caused as the initial reason the decline of the Mongolian pine trees, and also provided convenient conditions for the successful colonization of the woodwasp. The woodwasps attack the Mongolian pine trees infected by fungi and accelerated its decline.